2020
DOI: 10.1101/2020.02.03.932822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Latrophilins are essential for endothelial junctional fluid shear stress mechanotransduction

Abstract: Endothelial cell (EC) responses to fluid shear stress (FSS) are crucial for vascular development, adult physiology and disease. PECAM1 is an important transducer but earlier events remain poorly understood. We therefore investigated heterotrimeric G proteins in FSS sensing.Knockdown (KD) in ECs of single Gα proteins had little effect but combined depletion of Gαi and Gαq/11 blocked all known PECAM1-dependent responses. Re-expression of Gαi2 and Gαq but not Gαi1 and Gαi3 rescued these effects. Sequence alignmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…One particularly puzzling aspect of the current data on GPCRs in flow signaling is their redundancy. Multiple, distinct GPCRs reportedly mediate the same events downstream of flow 115,136,138,140,146 . Some of this overlap may be due to erroneous results or interpretations.…”
Section: Gpcrsmentioning
confidence: 99%
“…One particularly puzzling aspect of the current data on GPCRs in flow signaling is their redundancy. Multiple, distinct GPCRs reportedly mediate the same events downstream of flow 115,136,138,140,146 . Some of this overlap may be due to erroneous results or interpretations.…”
Section: Gpcrsmentioning
confidence: 99%
“…These findings fit well with the close proximity of all these players in cell-cell contacts. Recent data posted on BioRXIV report a requirement for the adhesion GPCR latrophilin-2, another junctional component (Tanaka et al, 2020). Latrophilin-2 is a GPCR studied mainly in neurons (Moreno-Salinas et al, 2019) but also expressed in ECs (Camillo et al, 2020;Tanaka et al, 2020).…”
Section: Shear Stressmentioning
confidence: 99%
“…Recent data posted on BioRXIV report a requirement for the adhesion GPCR latrophilin-2, another junctional component (Tanaka et al, 2020). Latrophilin-2 is a GPCR studied mainly in neurons (Moreno-Salinas et al, 2019) but also expressed in ECs (Camillo et al, 2020;Tanaka et al, 2020). This studied showed that it is required for flow activation of VEGFRs and downstream events via its GPCR function, and for flow activation of Notch signaling independent of G proteins (Tanaka et al, 2020).…”
Section: Shear Stressmentioning
confidence: 99%
See 2 more Smart Citations